Cost Estimation for Software Development Using Function Point Analysis Method - Lumba, Ester; Widyaningrum, Destriana; Waworuntu, Alexander (Universitas Multimedia Nusantara, 2024)
Software development requires substantial financial resources. This study aims to examine the cost estimation for software development. The complexity of the software, its intangibility as a non-physical product, the technology utilized, and human resources can all influence the determination of software development costs. The method used for cost estimation is Function Point Analysis with a case study approach. The researchers conducted a case study on the software development for an employee savings and loan cooperative at XYZ Company. The result of this study is a cost recommendation that can serve as a reference for selecting software development vendors by the cooperative's management.